A study on maintenance management system at residential college in IPTS / Nadiah Mohd Yusoff - Mohd Yusoff, Nadiah (Faculty of Architecture, Planning and Surveying, 2013)
Maintenance in the building is a process of reservation and restoration activity of the structure and components of a building. It covers the whole building which includes toilets, rooms, wall, roofs, drains, doors, windows, floors and also the fix furniture. Furthermore, the maintenance also involves in repair the lift system, mechanical and electrical system in the building. The issue of building maintenance is a universal issue and is highly considered in the early process of the construction (design) to assure the quality of the building. The purposed with research been held is to evaluate the effectiveness of building maintenance management system at residential college in IPTS. Furthermore, this study covered the maintenance management system presently implemented at residential college. Due to the maintenance management, the problems arise and satisfaction level among end users to maintenance management system at residential college. There are two types of research methodologies are qualitative and quantitative methodology used to completion of data and information from various sources. The methodology consists of three stages which collection of data (primary data and secondary data), analysis of data, result or findings from the data that been analyzed. Qualitative and quantitative research for this study involves the use of methodology such as interviews, observations, and analysis of document covering the topic. Questionnaire and documents review are also need the study on the building maintenance management system at residential college in IPTS. This study will be discussion about the background of each case study that had been selected. The case studies were selected at University Tenaga Nasional (UNITEN) and University Industri Selangor (UNISEL) at Klang Valley area. The respondent’s targets are 120 respondents which consist of staff and student at residential colleges. The conclusion of this study, the maintenance management was very important to the residential college and must gives more comfortable to the occupants. The maintenance management also must create a maintenance schedule so that maintenance work running smoothly and the entire work can been repaired. Other than that, the maintenance management also provided the good facilities and services to the occupant.